MOLECULAR CHARACTERIZATION OF NAGALAND LOCAL PIG (SUWO) USING MICRO SATELLITE MARKERS - G. Zaman; G. Kharghoria; M. K. Nath (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A set of 22 microsatellite markers recommended by Food and Agricultural Organization of United Nations (FAO) for Swine were used to study genetic diversity in Nagaland Local pig (Suwo) population. All the studied loci were highly informative and polymorphic. The number of observed alleles (Ne) detected ranged from 3 to 11, with an overall mean of 6.40±2.196. The mean effective number of alleles (Na) was 3.66±1.229. The frequency of allele ranged from 0.023 to 0.710. The mean PIC value was 0.3448 to 0.8175 was 0.65±0.127. The overall means for observed (Ho) and expected (He) heterozygosities were 0.62±0.224 and 0.69±0.116 respectively. The within breed estimate indicates heterozygosity shortage of 0.0887. The HardyWeinberg equilibrium test revealed that 9 out of 22 loci deviated from equilibrium. Shannon’s information index (I), was sufficiently high with a mean of 1.46. The population was stable with respect to size and was non-bottle necked.